Effects of Different Myofascial Trigger Point Release Techniques on Pain, Function and Quality of Lifef for Patients after Surgical Treatment of the Rotator Cuff - Greta Grigėnaitytė; Edgaras Lapinskas (Lithuanian Sports University, 2019)
Research background. Musculoskeletal pain in the shoulder joint is a major cause of non-traumatic upper limb pain (Tejera-Falcón et al., 2017). Miofascial release is a fast-moving form of manual therapy to reduce pain and restore soft tissue functions. Chronic pain relief in the movement apparatus is a major burden on health care systems and state economics due to the deteriorating quality of life of people experiencing these problems (Laimi et al., 2018). Research aim was to determine the eﬀect of diﬀerent myofascial trigger release techniques on pain, function and quality of life in patients after surgical treatment of rotator cuﬀ. Methods. The study included volunteers (n = 14) who met the selection criteria. Research methods included a VAS pain scale, active range of motion, isometric muscle strength and subjective assessment of functional changes (PSFS) and quality of life (SF-36). Results. After 14 days of physiotherapy exercises involving the release of myofascial trigger points, the intensity of pain decreased signifcantly from 5.6 ± 1.4 points to 1.8 ± 1.5 points (p < 0.05). After treatment of the range of motion, isometric muscle strength signifcantly increased (p < 0.05). The treatment used had a positive eﬀect on subjective functional changes (before 3.1 ± 0.8 points, followed by 7.8 ± 1.4 points, p < 0.05) and quality of life. Conclusion. The use of diﬀerent myofascial trigger release techniques is eﬀective in reducing myofascial trigger pain, improving function and quality of life in patients after surgical treatment of rotator cuﬀs. However, there were no statistically signifcant diﬀerences between the groups after treatment. Keywords: myofascial pain syndrome, myofascial trigger point, ischemic compression, soft tissue mobilization.